Translation theory in the age of Louis XIV : the 1683 De optimo genere interpretandi (On the best kind of translating) of Pierre-Daniel Huet (1630-1721) - Huet, Pierre-Daniel, 1630-1721 (Routledge, 2014)
Preeminent in a relatively rare category of separate early modern treatises on translation, the 1683 De optimo genere interpretandi by the polymath cleric Pierre-Daniel Huet (1630-1721) offers a concise introduction to its nature, history, theory, process and practice. Written in the form of a Ciceronian dialogue, On the best kind of translating not only represents Huet's acute and witty defence of the often disparaged literal or word for word model, but also provides illuminating glimpses into the critical and interpretive methods of his age. A guiding premise of this first modern edition and.